OPERATIONAL AND STRATEGIC CONTROLLING AS A TOOL FOR EFFECTIVE DEVELOPMENT OF INSURANCE COMPANIES - Ткаченко, Наталія; Селіверстова, Людмила (Socio-economic relations in the digital society, 2019)
Modern business conditions require investors and managers of insurance companies to take innovative approaches to the production of managerial decisions in the financial plane, that is why it is advisable to apply the ideas of controlling, through which the effective functioning of the company in the long run. The aim of the article is to investigate the peculiarities and importance of strategic and operational control in the activity of an insurance company and on this basis to find out the toolkit used in the decision-making process to ensure financial well-being and successful development of the company. The objectives of the insurance company were clarified and their classification was made taking into account different criteria, namely: by importance, by measurement, by terms of implementation, by coverage and by purpose. The importance of controlling as a system that aims to provide both coordination,  methodological and information support to the management of the company in the process of making management decisions, as well as to assess the internal capabilities and reserves of the insurer in a risky environment is substantiated. The essence, specific features and tasks of strategic controlling in the activity of an insurance company are determined to ensure competitive advantages, financial stability and its effective development. Strategic Control Toolkit has been identified. The basic elements of operational control are presented and its basic tools used in practical activity of insurers are specified. Attention is paid to the main differences between strategic and operational control of the insurer in terms of such positions as: targeting, time horizon, availability of alternatives, breadth of coverage, source, detail source, detail degree, accuracy of estimates and level of problems structuring.
Keywords: strategic controlling; operational controlling; strategy; financial stability; solvency; controlling tools; insurance company